Effect of different condiments and salt concentration on physico-chemical, microbiological and sensory properties of yoghurt spread (Indian Journal of Animal Production and Management, 2017)
An investigation was carried out to determine the effects of various condiments (mint, curry leaves and  green chilli @ 2.50% paste) and salt concentrations (1.00%, 1.25%, 1.50% and 2.00%) on proximate,  microbiological and sensory attributes of yoghurt spread. Yoghurt was prepared with NCDC 263 culture.  Significant differences were observed between the condiments used in respect of total solids (TS) (P
Keywords: Eating quality characteristics; Physico-chemical; Total aerobic count; Yoghurt spread